Ultrasound-guided blockade of the dorsal nerve of the penis in a Great Dane. (2nd December 2021) - Dagnall, Clare; Coss, Peter; Bird, Alice
Abstract : This report describes an approach to regional anaesthesia of the dorsal nerves of the penis in a Great Dane, as part of an anaesthetic protocol for surgical urethral resection and anastomosis. Bupivacaine (0.5%) was infiltrated around the left and right dorsal nerves of the penis, with ultrasound guidance. The locoregional approach was trans-perineal, with the ultrasound probe orientated at a right angle to the anus, at the level of the ischial symphysis. The described technique provided good visualisation of the urethra and dorsal arteries of the penis. No adverse events relating to the nerve blockade were encountered and no additional analgesia, other than the methadone premedication, was required intra-operatively. The locoregional approach was subsequently repeated on a cadaver using the same technique and, on dissection, demonstrated deposition of injectate next to the target neurovascular bundles. The technique described may provide a simple method of distal penile anaesthesia in the dog, where ultrasound is available.